Stepping Up, Sticking Together: Military Adolescents' Support of Their Civilian Parents and Concurrent Depression Symptoms. (21st December 2018) - Rodriguez, Aubrey J.; Margolin, Gayla
Abstract : The purposes of this study were to assess the ways adolescents in active-duty military families provide emotional and instrumental support to civilian mothers and to investigate the implications of such support for their own symptoms of depression. Eighty adolescents from active-duty military families provided self-report ratings of emotional and instrumental support rendered to their civilian mothers. Mother–adolescent dyads engaged in a 10-min discussion of military experiences, which was coded for adolescents' emotional validation of their mothers. Path analyses showed that adolescents who provided more instrumental support and showed more emotional validation reported fewer symptoms of depression. However, adolescents' instrumental support to the mother was not inversely associated with their depression symptoms when the mothers reported high depression symptoms. Recent military demands did not moderate associations between adolescent support and depression symptoms. In this, the first study to our knowledge assessing youth-to-parent support provision among military adolescents, results suggest that emotional validation and instrumental support given at will by adolescents to their civilian mothers are associated with lower levels of adolescent depressive symptoms. Results also underscore the impact of maternal depression on family processes and emphasize the importance of careful assessment of support processes within military families.